Analysis of the applicability of consultancy services in works projects on Local Government Authority in Tanzania : A case of Kahama District Council - Karumbete, Mvano Amani (Mzumbe University, 2024)
A Dissertation Submitted in Partial/Fulfilment of the Requirements for Award of the degree of Master of Science in Procurement and Supply Chain Management of Mzumbe University 2013